Penerapan Terapi Behaviorisme dalam Upaya Perbaikan Akhlak Siswa di Lingkungan Sekolah - Muhammad Ghifan Rizqulah; Umi Nur Kholifah (Indo Publishing, 2026)
This article discusses the application of behaviorism therapy as an approach to improve student morals. Behaviorism therapy is an approach to psychology that focuses on observable and changed behavior. The goal of this therapy is to identify behaviors that are not in accordance with the desired moral values, eliminate negative behaviors, and replace them with positive behaviors. This article outlines some important steps in the application of behaviorism therapy to improve student morals. As well as measures to link such behavior to unpleasant consequences, such as punishment or adverse social consequences. In addition, this article also discusses positive reinforcement as one of the strategies of behaviorism therapy. This article also covers the gradual use of shaping or shaping the desired behavior. College students can be given positive reinforcement when they show progress in changing their negative behavior into a better behavior. This article hopes that the application of behaviorism therapy in an effort to improve student morals can make a positive contribution in shaping better behavior and creating a more ethical and moral academic environment.